2004
DOI: 10.1073/pnas.0407971101
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genetic analysis of disseminated neoplastic cells in lymphangioleiomyomatosis

Abstract: loss of heterozygosity ͉ metastasis ͉ CD235a ͉ angiomyolipoma ͉ smooth muscle cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
122
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 27 publications
8
122
0
4
Order By: Relevance
“…Further, LAM cells were identified in blood and other body fluids (ie, urine, chylous pleural effusions, ascites). 17 These data are consistent with the metastatic spread of LAM cells among organs.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Further, LAM cells were identified in blood and other body fluids (ie, urine, chylous pleural effusions, ascites). 17 These data are consistent with the metastatic spread of LAM cells among organs.…”
supporting
confidence: 80%
“…Plasma levels of osteopontin (a protein that binds to CD44) were higher in LAM patients than in healthy volunteers, 23 and LAM cells from blood or chyle can be characterized for TSC2 LOH. 17 These, in addition to VEGF-D, may aid in the difficult diagnosis of a patient who presents with only cystic lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that estrogen treatment enhances the survival of intravenously injected cells in the peripheral blood. These data are of particular interest because circulating LAM cells can be detected in the blood and pleural fluid of women with LAM (35). Our data provide a rationale for the potential use of circulating cells as a quantitative and rapid biomarker of response to targeted therapy in women with LAM.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it has been postulated that LAM may originate from AML cells that metastasize to the lungs. 14,15 Against this possibility, however, stands the fact that the two conditions are more often seen independently than in combination and that AML affects men and women, whereas LAM rarely affects men. Therefore, currently it is hypothesized that TSC2-deficient cells from a third site may metastasize to both the lung and the kidney in the sporadic form of LAM.…”
mentioning
confidence: 99%
“…Therefore, currently it is hypothesized that TSC2-deficient cells from a third site may metastasize to both the lung and the kidney in the sporadic form of LAM. 16 Despite intense speculation, 14,15,17 the precursor cell from which AML and LAM originate remains unknown. A neural crest cell (NCC) origin has been mostly favored 14,15,17 because of the coexistence of melanocytic and smooth cell markers in the AML and LAM cells, two cell lineages known to arise, partially in the case of smooth muscle cells, from NCCs.…”
mentioning
confidence: 99%